2020
DOI: 10.3389/fpsyg.2020.546187
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About Children’s Memory and Child Investigative Interviewing Practices: A Survey in Dutch Child Protection Professionals from ‘Safe Home’

Abstract: Knowledge of children's memory and forensic interviewing skills are crucial in child abuse investigations. Safe Home is the Dutch hotline where both professionals and citizens can report concerns about child abuse or domestic violence. Professionals at Safe Home often serve as first responders to determine the need for a child abuse investigation, protective measures and/or further police investigation. In this study, child protection professionals (N = 158) employed at Safe Home (i.e., behavioral scientists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…This forced choice procedure has been used in previous related work as well (e.g. see Erens et al (2020) using a forced choice method with a Dutch sample).…”
Section: Methodsmentioning
confidence: 99%
“…This forced choice procedure has been used in previous related work as well (e.g. see Erens et al (2020) using a forced choice method with a Dutch sample).…”
Section: Methodsmentioning
confidence: 99%
“…They found that 75.7% ( n = 108) agreed that they could. In a recent study, 84% ( n = 133) of Dutch child-protection workers indicated that traumatic memories are often repressed (Erens, Otgaar, Patihis, & De Ruiter, 2019).…”
Section: Memory Beliefs About Repressed Memories: From Then To Nowmentioning
confidence: 99%
“…In addition, because the items used differed to some extent among survey studies, we concentrated on statements for which people were asked specifically about the frequency of repressed memories (e.g., “Traumatic memories are often repressed”). When we focused on these statements (Erens et al, 2019; Kagee & Breet, 2015; Patihis et al, 2014), we found that 78% ( n = 618) of surveyed people believed that traumatic experiences are often repressed. We also compared the rates of belief in repressed memories in the 1990s with those of all studies performed after the 1990s.…”
Section: Memory Beliefs About Repressed Memories: From Then To Nowmentioning
confidence: 99%
“…Participants were asked to indicate whether they thought each statement is ‘true’ or ‘false’, or they could select the ‘don't know’ option. Of the 20 statements, 19 are false based on broad scientific consensus (see Erens et al, 2020; Sumampouw et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Quas et al's study (2005) in California showed substantial variability in jury‐eligible students' knowledge about children's memory, suggestibility, and reactions to sexual abuse; some beliefs were compatible with scientific research findings (e.g., children can be suggestible about events they do not understand) while others were not (e.g., children can remember sexual abuse that occurred during infancy). A survey conducted by Erens et al (2020) revealed that many social workers, behavioural scientists, and medical doctors in the Netherlands agreed that repressed memories can be retrieved accurately using certain therapeutic techniques, despite such an argument running counter to current memory research (see Otgaar et al, 2019; see also Dodier & Otgaar, 2019).…”
Section: Introductionmentioning
confidence: 99%